(3GdSja GdegfO aj SjQI Gdedc GdeDjOs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj fUH Ydi YHGOg SQGObGJ GdYR s
(3BNQgG (B:s
(3Edi gfG Je eG CYJfj HLeYI GdTjN GdEeGe HOQGdOjf GdYjfj QMeg Gddg s
(3VefgG SjQI Gdedc GdeDjO CHj GdfUQ TjN GdMehOj GdPi Jhdi edc eUQ (B815 - 824 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B150s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B53 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eUhQI Yf fSNI HGQjS Qbe (B675) ((3JGQjN (B1585) s
Keywords: (3GdJGQjNs